Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10661-005-1011-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of elemental contaminants in water and fish samples from Aba river

Abstract: The elemental contaminants in water and fish samples from Aba river were studied. The elements studied were Zn, Ni, As, Hg, Co and Mn. Three water samples and three samples of different fish species were collected from different locations in the river. The water and fish samples were analysed for elemental contaminants using Atomic Absorption Spectrophotometer (AAS). The elemental toxicants Zn and Mn were identified in appreciable amounts in fresh fish species namely, Lates niloticus and Oriochronis niloticus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 16 publications
(13 reference statements)
2
17
0
Order By: Relevance
“…This nominal concentration resulted in a concentration of total Hg of 106 g L −1 in the contaminated water evaluated by Cold Vapor Atomic Fluorescence Spectrometry (CV-AFS) according to the USEPA 1631 detection technique (USEPA, 2002). Concentrations of total Hg ranging from 1 to 230 g L −1 are usually detected in water bodies near industrialized areas (Hypolito et al, 2004;Alinnor, 2005;Bollen et al, 2008).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This nominal concentration resulted in a concentration of total Hg of 106 g L −1 in the contaminated water evaluated by Cold Vapor Atomic Fluorescence Spectrometry (CV-AFS) according to the USEPA 1631 detection technique (USEPA, 2002). Concentrations of total Hg ranging from 1 to 230 g L −1 are usually detected in water bodies near industrialized areas (Hypolito et al, 2004;Alinnor, 2005;Bollen et al, 2008).…”
Section: Experimental Designmentioning
confidence: 99%
“…Studies have been shown that near gold mining and/or industrial discharges, levels of the total Hg in surrounding water can reach values from 0.0001 to 19.82 mg L −1 (Alinnor, 2005;Serfor-Armah et al, 2005;Gammons et al, 2006;Bollen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…After 24 h, the water was renewed and the HgCl 2 group was submitted to a nominal concentration of 150 lg L -1 of HgCl 2 (20% of LC 50 -96 h). Concentrations of total mercury ranging from 0.001 to 0.230 mg L -1 are usually detected in water bodies near industrialized areas (Hypolito et al 2004;Alinnor 2005;Bollen et al 2008).…”
Section: Experimental Designmentioning
confidence: 99%
“…Although the industrial use of Hg has been reduced in recent years due to stricter regulations, high concentrations of Hg have been found in water samples at the sites with extensive industrial activities, mainly chloro-alkali, pulp and paper and ceramic industries. In these areas, total Hg concentrations ranged from 0.0005 to 0.23 mg L -1 (Hypolito et al 2004;Alinnor 2005;Bollen et al 2008). Shaw et al (1989) found mercury levels ranging from 1.50 mg L -1 in effluents discharged by chloro-alkali industries.…”
Section: Introductionmentioning
confidence: 98%
“…Aquatic ecosystems are sensitive to exposure of toxic contaminants and heavy metals. Among the aquatic organisms, fish is most vulnerable to these contaminants (Alinnor, 2005). Lead is a naturally occurring heavy metal present in the earth's crust, rocks, soil and water.…”
Section: Introductionmentioning
confidence: 99%